Bi-Threshold Cooperative Spectrum Sensing With the Ability of Simultaneous Improving Throughput and Reducing Energy Consumption in Cognitive Radio Network - Masoud Moradkhani; Farzad Soltanian (مهندسی مخابرات جنوب)
By performing cooperative spectrum sensing in a cognitive radio network, although the network throughput increases with the increase in the number of secondary users, but at the same time, it also causes an increase in energy consumption. This makes it necessary to provide a system that is able to create a tradeoff between throughput and energy consumption. In contrast to the conventional method of spectrum sensing based on one detection threshold, spectrum sensing with double thresholds avoids reporting unreliable data to the fusion center, thus potentially leading to greater energy saving. In this paper, a double threshold spectrum sensing cognitive radio network with a non-ideal reporting channel is optimized. The values of the threshold and the sensing time are jointly optimized to maximize the throughput of the network, provided that the network energy consumption and the amount of interference with the primary users are limited. The optimization problem is formulated and a numerical method is presented to solve it. The simulation results show a flexible system that can simultaneously provide higher throughput and lower energy consumption than the conventional sensing method. These results, while confirming the higher tolerance against the error of the reporting channel, show a significant energy saving of up to 70% by guaranteeing the throughput efficiency greater than 1.